Adaptive downregulation of mitochondrial function in down syndrome. - Helguera, Pablo Rodolfo (2013)
Mitochondrial dysfunction and oxidative stress are common features of Down syndrome (DS). However, the underlying mechanisms are not known. We investigated the relationship between abnormal energy metabolism and oxidative stress with transcriptional and functional changes in DS cells. Impaired mitochondrial activity correlated with altered mitochondrial morphology. Increasing fusion capacity prevented morphological but not functional alterations in DS mitochondria. Sustained stimulation restored mitochondrial functional parameters but increased reactive oxygen species production and cell damage, suggesting that reduced DS mitochondrial activity is an adaptive response for avoiding injury and preserving basic cellular functions. Network analysis of genes overexpressed in DS cells demonstrated functional integration in pathways involved in energy metabolism and oxidative stress. Thus, although preventing extensive oxidative damage, mitochondrial downregulation may contribute to increased susceptibility of individuals with DS to clinical conditions in which altered energy metabolism may play a role, such as Alzheimer’s disease, diabetes, and some types of autistic spectrum disorders.